2020
DOI: 10.26434/chemrxiv.12568595.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sea Urchin Pigments as Potential Therapeutic Agents Against the Spike Protein of SARS-CoV-2 Based on in Silico Analysis

Abstract: Several studies have been published regarding the interaction between the spike protein of the novel coronavirus SARS-CoV-2 and ACE2 receptor in the host cells. In the presente work, we evaluated the in silico properties of two sea urchin pigments, Echinochrome A (EchA) and Spinochromes (SpinA) against the Spike protein (S) towards finding a potential therapeutic drug against the disease caused by the novel coronavirus (COVID-19). The best ensemble docking pose of EchaA and SpinA showed a binding affinity of -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
0
6
0
1
Order By: Relevance
“…40 and 41). Barbieri's group [91] reported sea urchin pigments against the ACE2-spike domain as potential therapeutic agents in in silico studies. Sea urchin pigments are a very interesting group of bioactive compounds that not only have anti-viral and anti-bacterial properties but also reduce reactive oxygen species (ROS) stress.…”
Section: Mln-4760mentioning
confidence: 99%
“…40 and 41). Barbieri's group [91] reported sea urchin pigments against the ACE2-spike domain as potential therapeutic agents in in silico studies. Sea urchin pigments are a very interesting group of bioactive compounds that not only have anti-viral and anti-bacterial properties but also reduce reactive oxygen species (ROS) stress.…”
Section: Mln-4760mentioning
confidence: 99%
“…In the global context, it is necessary to continue to analyze risks in order to bring flexibility to the business model. For example, in a pandemic scenario, this innovative and flexible approach allowed ARBACIA to explore the possibility of using its products for SARS-CoV-2 and there have been satisfactory results to date (Barbieri et al, 2020;Rubilar et al, 2020). ARBA-CIA has developed the sea-tech and business model by using agro ecological principles in its land-based operations (FAO, 2018).…”
Section: Innovative Approachesmentioning
confidence: 99%
“…However, in the 1980s, the USSR pharmaceutical industry initiated the first studies on naphthoquinone pigments, commonly known as Spinochromes, from sea urchins in the Far East of Russia. Russian scientists found that Echinochrome A, a molecule belonging to the spinochrome family, extracted from the testes and spines has cardioprotective action and healing properties for ocular diseases and they developed two drugs, "Histochrome" and "Gistochrome" which were commercially approved in Russia (FSP R002363/02-260213 Manufacturer's Pharmacopeia Article; Mischenko, Fedoreyev & Bagirova, 2003;US6410601B2;Mischenko et al, 2005;Lebed'ko, Ryzhavskii, & Demidova, 2015;Vasileva, Mischenko, & Fedoreyev, 2017;Fedoreyev et al, 2018a;Fedoreyev et al, 2018b;Shikov, Pozharitskaya, Krishtopina, & Makarov, 2018;Yoon et al, 2019;Oh et al, 2019;Barbieri et al, 2020;Rubilar et al, 2020). There are also biologically active foods being developed with naphthoquinone pigments from sea urchins, such as Thymarin, Sea Hematogen and AXIVOS® (Table 1).…”
mentioning
confidence: 99%
“…Avances al 2020: El erizo de mar A. dufresnii no había sido estudiada desde los años 80s. Se han realizado varios estudios in vitro utilizando química computacional, y protocolos validados a nivel internacional para medir el efecto del 1,4-naftoquinona polihidroxilasa (Echinocromo A), en el coronavirus SARS-CoV-2 (Rubilar et al, 2020;Barbieri et al, 2020).…”
Section: Arbacia Dufresnii (Blainville 1825)unclassified